Association of Thyroid Function with Early/Mid-term Aorta-Related Adverse Events and Readmissions after Thoracic Endovascular Aortic Repair - Lu, Nan (Sci Rep, 2017)
The prognosis of patients after thoracic endovascular aortic repair (TEVAR) is affected by several clinical characteristics. This study aimed to evaluate whether thyroid hormones predicts early (30 days) and mid-term (12 months) aorta-related adverse events (ARAE) and readmissions (ARAR) in patients after TEVAR. A total of 338 continuous patients who underwent TEVAR were included and stratified based on quartile of free thyroxine (FT4) levels examined before surgery. The relationship of FT4 levels with early or mid-term ARAE and ARAR were assessed using univariate and multiple logistic regression analysis. The incidence of ARAE and ARAR were 2.7% and 4.1% within 30 days, and 8.9% and 13.5% within 12 months, respectively. After adjusting for confounders, the lowest FT4 quartile group were noted to be at significantly greater risk than the highest FT4 quartile group in early (OR 10.105, 95% CI 1.103 to 92.615, P = 0.041) and mid-term (OR 5.687, 95% CI 1.708 to 18.935, P = 0.005) ARAR, but not significantly different in early (OR 2.097, 95% CI 0.228 to 19.307, P = 0.513) and mid-term (OR 0.695, 95% CI 0.207 to 2.332, P = 0.556) ARAE. Thus, patients with low-normal FT4 levels after TEVAR are at greater risk of ARAR, but not ARAE, in both the early and the mid-term follow-up periods.